The Direction of the City Gas as Clean Energy in Indonesia with the Work Force as the Moderator - Prima Andry; Pramadika Havidh; Dahani Wiwik; Rinanti Astri; Uno Prana Ugiana (E3S Web of Conferences, 2024)
The distribution of city gas to consumers as clean energy has expanded. Despite its expansion, the trend can run into a drop in consumer demand. This can be the case if factors that control its growth are improperly managed. Hence, regulating the variables are of critical relevance. The data movement from year to year continues to show an expanding tendency with reference to the Indonesian city gas industry. This study can further improve knowledge of Indonesia's city gas distribution industry and to paint a clearer picture of a number of latent variables that need to be taken into account in order to distribute natural gas to Indonesian cities as efficiently as possible. The Structured Equation Technique (SEM)was the methodology employed in this investigation. In a more detailed explanation, the association between indicators and latent variables is examined using path analysis, which is derived from multivariate regression, in order to assess the validity of the multiple regression model. In keeping with the research methodology, data from indicators of city gas distribution companies during the period 2010-2020 were grouped and sorted by the Indonesian Central Statistics Agency. These indicators included income, the number of employees paid, the volume of city gas distributed, and operational costs. The purpose of this research is to produce information that can be used by the government and other stakeholders to accelerate the development of Indonesia's gas distribution business. This study's novelty or worth lies in its ability to shed light on the influence of latent variables that hold the status as moderating variables. Study limitations: Because non-disclosure primary data are not readily available and secondary data are scarce, it is assumed that the information from the Indonesian Central Statistics Agency is reliable and can be used to describe the explanatory variables of the city gas distribution industry in Indonesia.